Alignment of Parent and Child Self-Report of Bilingual Language Experience and Proficiency - John Gallagher; Amy Pratt; Elizabeth D. Peña; Ashley Sanabria (Language, Speech, and Hearing Services in Schools, 2026)
Introduction: Information pertaining to language experience and proficiency is crucial in studies of bilingual children and is usually sought from parents. However, there are barriers to obtaining valid information from parents, which may be addressed by child's self-report. In this study, we examined the relationships between parent report and child self-report, including whether relationships differ by child's grade level. Method: Parent and child questionnaires were analyzed from n = 489 Spanish/English bilinguals in prekindergarten through third grade ( M age = 7.24). Both questionnaires resulted in measures of proficiency in Spanish and English as well as bilingual experience. Results: Child questionnaires administered directly to the child yielded higher response rates (93%) than questionnaires sent home for parents (31%). Correlations between similar indicators of proficiency and experience across child and parent reporters ranged from medium to large. Multiple regression analyses revealed that grade level was a significant predictor of child's self-reported proficiency in both languages but not of bilingual experience. Results did not conclusively demonstrate that parent and child alignment differed by child's grade level. Conclusions: Although child's self-report is not a replacement for parent report, research with young bilinguals should consider the use of a child's self-report tool, particularly when low response rates to parent questionnaires are a concern. Child self-report and parent report are moderately to strongly correlated, and seeking a child's self-report provides a unique perspective on their bilingual language proficiency and experience.